STUDENTS’ PERCEPTIONS OF M-READER - Rajabpour, Abouzar (TEFLIN Journal, 2020)
Many universities in the Middle East, for instance, Shiraz University in Iran and Sultan Qaboos University in Oman have been running M-reader, a free Internet site which helps educational institutions to manage extensive reading (ER), as a way of including Extensive Reading in ELT classes for years. In spite of few attempts to evaluate this online tool based on different aspects, no studies have focused on students’ ideas toward the pros and cons of M-reader and how it can be improved. Hence, using a large sample, the present study sheds some light on potential advantages and drawbacks of M-reader and, ultimately, presents students’ comments on how to idealize this popular Extensive Reading tool. A mixed-method design was used in data collection and data analysis. The study shows that M-reader is a popular online platform among students despite some potential drawbacks.